Designing responsible research and innovation to encourage serendipity could enhance the broader societal impacts of research. Issue 1 (2nd January 2019) - Holbrook, J. Britt
ABSTRACT: This article argues that (i) RRI should be conceived as a tool; (ii) RRI can be used to enhance the broader societal impacts of research; and (iii) designing RRI specifically to encourage serendipity is the best choice to achieve the goal of enhancing the broader societal impacts of research.